2004
DOI: 10.1029/2004jf000172
|View full text |Cite
|
Sign up to set email alerts
|

Threshold phenomena in erosion driven by subsurface flow

Abstract: [1] We study channelization and slope destabilization driven by subsurface (groundwater) flow in a laboratory experiment. The pressure of the water entering the sand pile from below as well as the slope of the sand pile are varied. We present quantitative understanding of the three modes of sediment mobilization in this experiment: surface erosion, fluidization, and slumping. The onset of erosion is controlled not only by shear stresses caused by surfical flows but also by hydrodynamic stresses deriving from s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 29 publications
1
53
1
Order By: Relevance
“…where f ϭfluid density; gϭgravitational acceleration; dϭgrain Lobkovsky et al 2004͒. This research extends such seepage erosion experiments for simulating natural streambank profiles with much larger slopes and investigated the combined erosion of seepage and bank failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where f ϭfluid density; gϭgravitational acceleration; dϭgrain Lobkovsky et al 2004͒. This research extends such seepage erosion experiments for simulating natural streambank profiles with much larger slopes and investigated the combined erosion of seepage and bank failure.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated sediment from subsurface induced streambank failure must be removed for continued subsurface flow erosion. Research has begun to investigate the interaction of surface erosion, fluidization, and slumping whereby the onset of erosion is controlled not only by surficial flows but also hydrodynamic stress from groundwater seepage ͑Lobkovsky et al 2004;Worman 1993͒. Indoor flume studies indicate that surface erosion rates increase by an order of magnitude when unsaturated pore-water pressures increase to near saturation, thereby decreasing the soil shear strength ͑Rockwell 2002; Owoputi and Stolte 2001͒.…”
Section: Introductionmentioning
confidence: 99%
“…These types of failures are often referred to as pop out or tension failures. Lobkovsky et al (2004) showed that seepage force is proportional to the hydraulic gradient with the following relationship:…”
Section: Introductionmentioning
confidence: 99%
“…When seepage occurs, seepage gradient forces (SF) exert body forces on streambank sediment proportional to the hydraulic gradient (Lobkovsky et al, 2004;Chu-Agor et al, 2009):…”
Section: Introductionmentioning
confidence: 99%